Making end-of-life health disparities in the U.S. visible through family bereavement narratives - Cassidy Taladay-Carter (Elsevier, 2024)
Objective: End-of-life experiences can have important implications for the meaning-making and communication of bereaved family members, particularly due to (in)access to formal healthcare services (i.e., palliative care and hospice). Grounded in Communicated Narrative Sense-Making theory, this study extends knowledge about how the stories told about end-of-life by bereaved family members affect and reflect their sense-making, well-being and importantly, potential disparities in end-of-life care. Methods: Semi-structured interviews with 25 bereaved individuals were conducted regarding their experiences with the terminal illness and death of an immediate family member. Using a framework of family bereavement narratives, a cross-case data analysis demonstrated qualitative patterns between (in)access to end-of-life care and how participants framed bereavement stories. Results: Four themes illustrated the continuum of communication that families engaged in when making sense of end-of-life experiences, including reflections on silence, tempered frustrations, comfort with care, and support from beyond. Innovation: This innovative qualitative connection between family members' bereavement stories and end-of-life care emphasizes the importance of employing a health equity lens within hospice and palliative care, especially in addressing the important aim of comprehensively supporting families even when illness ends. This study demonstrates that access to, quality of, and imagining beyond current structures for EOL may be vital factors for facilitating effective sense-making for the dying and their family systems. Conclusion: These findings illustrate the potential interconnections between (in)access to end-of-life care, sense-making, and communication for individuals and families experiencing terminal illness and bereavement.